Production of natural hand sanitizers from Aloe vera (Aloe vera), Rambutan (Nephelium lappaceum L.) and Lime (Citrus aurantiifolia) skins, Betel leaf (Piper betle) and Eucalyptus grandis leaves - Taufik, Muhammad; Cahyady, Bobby; Razali, Mariany; Ardilla, Desi (Journal of Saintech Transfer, 2021)
The utilization of plant parts that are not used is very important in order to minimize organic waste. Rambutan (Nephelium lappaceum L.) rind has antibacterial properties which can be used as raw material. The same goes for the skin of lime peel (Citrus aurantiifolia), Betel leaf (Piper betle), Aloe vera (Aloe vera) and Eucalyptus grandis leaves. Eucalyptus grandis is a product that is not harvested in Industrial Plantation Forests which are grown by the community and green Industry in North Sumatra. The part used is the plant stem which is used as a material for making pulping. The extraction process was carried out used steam distillation. In this work, the analysis of active compound used GCMS instrument. The result of the analysis showed that there was 1.8 Sineol as much as 52%. This compound was used as an antiseptic and give a fragrant aroma. This work aims to produced of natural hand sanitizers used Eucalyptus grandis as an odorant and antiseptic agent which used to prevent the transmission of Covid19 in Kotamatsum IV sub district, Medan City. The resulting product was a hand sanitizer that is safe to use and friendly to the environment. The natural hand sanitizer products can be used by the community in reducing the transmission of Covid19 and can increase people’s income.